A differential game-theoretic model of auditing for data storage in cloud computing. (2017) - Li, Zhi; Liu, Yanzhu
Cloud computing is a novel computing model that enables convenient and on-demand access to a shared pool of configurable computing resources. Owing to data outsourcing, this new paradigm of data hosting service is also facing many new security challenges. Auditing is essential to make sure that the user's data is correctly stored in the cloud. In this article, the interaction between cloud user and cloud service providers (CSPs) in cloud as a non-cooperative differential game has been studied. In this game formulation, a feedback Nash equilibrium of the game is reviewed and complex decision making processes and interactions between cloud user and CSPs are analysed. The simulation results provide a reference for users and CSPs in setting appropriate energy consumption and optimal strategies.